Analisis Kinerja dan Risiko Rantai Pasok Operasional Armada Pelabuhan menggunakan Model SCOR dan House of Risk (HOR) pada PT Berkah Jaya - Haura Nurhaliza; Riska Kartika Sari; Okta Fitriana; Andini Reva Aprillia; Nuralyah Nuralyah (Jurnal Logic: Logistics & Supply Chain Center, 2026)
Port fleet operations play a crucial role in ensuring smooth logistics distribution, but are vulnerable to various risks that can disrupt supply chain performance. This study aims to analyze the performance and risks of PT Berkah Jaya's port fleet operations using an integration of the Supply Chain Operations Reference (SCOR) and House of Risk (HOR) models. The study employed a quantitative descriptive approach with data collection through observation, interviews, and documentation. The SCOR model was used to map business processes into five main processes: Plan, Source, Make, Deliver, and Return, while the HOR method was used to identify risk events and risk agents, prioritize risks based on the Aggregate Risk Potential (ARP) value, and formulate mitigation strategies through the Effectiveness to Difficulty Ratio (ETD). The results showed that PT Berkah Jaya's supply chain processes had been systematically mapped and successfully identified 27 risk events and 29 risk agents that could potentially disrupt operations. Pareto analysis showed that most potential risks stemmed from a number of priority risk agents, such as ship delays, fleet damage, document delays, and weather conditions. Recommended mitigation strategies include preventive maintenance, administrative digitization, operational scheduling optimization, improved coordination, and strengthened occupational safety implementation. The integration of SCOR and HOR has proven to be an effective approach to improving the performance and risk management of port fleet operational supply chains.